Primary prevention of physical and mental handicaps: Genetic counselling and prenatal diagnosis - J. Hof (AOSIS, 1982)
To date there are no figures available on the number of handicapped people in the Republic of South Africa. The lack of an adequate method of assessment and the difficulty of defining the different handicaps are the major obstacles.